Microstructure, Texture and Mechanical Properties in a Low Carbon Steel After Ultrafast Heating - Monsalve-Gonzalez, A; Castro-Cerda, F (Elsevier Ltd, 2016)
Heating experiments in a wide range of heating rates from 10 °C/s to 1200 °C/s and subsequent quenching without isothermal soaking have been carried out on a low carbon steel. The thermal cycles were run on two different cold rolled microstructures, namely ferrite+pearlite and ferrite+martensite. It is shown that the average ferritic grain size, the ferrite grain size distribution, the phase volume fractions and the corresponding mechanical properties (ultimate tensile strength and ductility) after quenching are strongly influenced by the heating rates and the initial microstructure. The ferrite grain size distribution is significantly modified by the heating rate, showing a markedly bimodal distribution after fast annealing. The rise of the heating rate has produced a change in the relative intensities of texture components, favouring those of the cold-deformed structure (RD fibre) over the recrystallization components (ND fibre). © 2016 Elsevier B.V.